"It feels like sending your children into the lions' den" – A qualitative investigation into parental attitudes towards ASD inclusion, and the impact of mainstream education on their child. (January 2022) - McKinlay, Jack; Wilson, Claire; Hendry, Gillian; Ballantyne, Carrie
Highlights: Four themes were identified as important to parents' expereinces of their autistic child's mainstram education. Parents were concerned about the use of appropriate inclusive strategies to support their child's learning. Parents believed that their child may be isolated from their peers and associated schooling with their child's mental health. Schools and staff must listen to and empathise with parents regarding their concerns about their child's needs. Abstract: Background: Increasing numbers of autistic children are being educated in mainstream schools. The success of inclusive education is dependent upon multiple factors, including key stakeholders (i.e., teachers and parents). Research has tended to focus on teachers' experiences of inclusion with limited focus on parents. Aims: The study aimed to qualitatively investigate parental attitudes and experiences of inclusive education. As such, the research question was: What are attitudes towards, and experiences of, inclusive education for parents of autistic children? Methods and procedure: Semi-structured interviews were conducted with 12 parents of autistic children. Data was analysed using Thematic Analysis (Braun & Clarke, 2006). Outcomes and results: four themes were identified; 1) Feeling Unheard; 2) Implementation of Inclusive Strategies; 3) Social Exclusion; 4) Mental Health and Wellbeing Impact. Findings suggested that parents felt their child struggled socially in mainstream school, with such experiences negatively impacting upon their child's wellbeing. The detrimental impacts were a result of parents believing school staff dismissed their concerns and thus appropriate strategies for their child were not always implemented. Conclusions and implications: This highlights the need for school staff and parents to work together to enhance inclusivity both academically and socially for autistic children.